Analisis Lingkungan Kewirausahaan: Studi Kasus Pada Siswa Kelas XII SMK - Tammie, Tieke Amaluthnvie; Nuryanti, B. Lena; Utama, Rd. Dian Herdiana (Universitas Pendidikan Indonesia, 2018)
This study aims to determine the analysis of entrepreneurial environment and entrepreneurial motivastion at student grade XII in SMK Negeri 1 Cimahi. This research uses descriptive approach with explanatory survey method. The studentÂ analysis unit is 167Â people . Data collection using questionnaire. The analysis technique used is descriptive technique by using frequency distribution. The result showed that entrepreneurial environment is in average category andÂ entrepreneurial motivation is in average category. The differences in this study located on an object research, time research, a measuring instrument , literature that used , the theory that is used and the results of the study